A Hyperactive Form of unc-13 Enhances Ca(2+) Sensitivity and Synaptic Vesicle Release Probability in C. elegans - Li, Lei (Cell Rep, 2019)
Munc13 proteins play several roles in regulating shortterm synaptic plasticity. However, the underlying molecular mechanisms remain largely unclear. Here we report that C. elegans UNC-13L, a Munc13-1 ortholog, has three domains that inhibit synaptic vesicle (SV) exocytosis. These include the X (sequence between C2A and C1), C1, and C2B domains. Deleting all three inhibitory domains produces a hyperactive UNC-13 (sUNC-13) that exhibits dramatically increased neurotransmitter release, Ca(2+) sensitivity of release, and release probability. The vesicular pool in unc-13 mutants rescued by sUNC-13 exhibits a faster synaptic recovery and replenishment rate, demonstrating an important role of sUNC-13 in regulating synaptic plasticity. Analysis of double mutants suggests that sUNC-13 enhances tonic release by increasing the open probability of UNC-64/syntaxin-1A, whereas its effects on evoked release appear to be mediated by additional functions, presumably by further regulating the activity of the assembled soluble N-ethylmaleimide-sensitive factor activating protein receptor (SNARE) complex.